Carrier Recombination Times in Amorphous-Silicon Doping Superlattices - Hundhausen, Martin; Ley, Lothar; et al. (Physical Review Letters, 1984)
Doping superlattices, i.e., multilayer structures consisting of ultrathin (50 < d< 400 ) n-type, intrinsic, and p-type layers of a-Si: H (nipi structures), have been produced. Up to a tenfold increase in their infrared photoconductivity after band-gap illumination compared to unstructured a-Si: H is observed. The results are well described by a simple model for the carrier recombination kinetics that takes into account the spatial separation of electrons and holes due to the modulation of the band energies. © 1984 The American Physical Society.
UnivIS-Import:2015-03-05:Pub.1984.nat.dphy.IAP.exphys.carrie_2